PERILAKU PETERNAK TENTANG PEMBUATAN RANSUM BERBASIS BAHAN LOKAL DI GAPOKTAN URIPMULYO DESA PAREREJO PURWODADI PASURUAN - Cecep Solihin; Wahyu Windari; Novita Dewi Kristanti (Fapetrik-UMPAR, 2019)
Uripmulyo Gapoktan is an association for farmer groups in Parerejo Village, which consists of Uripmulyo I, Uripmulyo II, Uripmulyo III, Mulyo Tani, Suka Makmur and Tani Makmur Farmers groups. This farmer group has a population of 464 cattles. In addition, in the Parerejo Village, there was a tofu factory and rice mill industry, whose waste is not utilized as a beef cattle ration. Farmers only provide forage feed, so it is necessary to carry out counseling activities on the manufacture of rations based on local ingredients, in the form of materials that were easily found by local farmers or potential feed ingredients in Parerejo Village. These feed ingredients include grass, tofu dregs, and rice bran and additional premixes. This study was conducted on 50 beef cattle breeders who were incorporated into the Uripmulyo Gapoktan taken randomly. The aim was to find out the knowledge, attitudes, and skills of breeders towards making rations based on local ingredients for beef cattle feed in Gapoktan Uripmulyo, Parerejo Village, Purwodadi District, Pasuruan Regency. The method used in this study includes four stages, namely (1) counseling in class, (2) counseling with demonstration methods, (3) counseling practice / out class (4) evaluation. The extension media used were (1) powerpoint slides, (2) folders, (3) videos and (4) real objects. Analysis techniques used in behavioral measurement include, (1) knowledge using interval techniques, (2) attitude measurement using T-score techniques and (3) observational skills measurements and analyzed using interval techniques. The results of the implementation showed that the level of knowledge of farmers was 76% in the good category, attitudes of farmers showed 74% received, and the level of skills of farmers showed 86% were very skilled at the material presented, about how to make rations based on local ingredients for beef cattle feed.